DESKRIPSI SEMUT PADA HABITAT TERTUTUP DAN TERBUKA DI KAWASAN HUTAN KOTA ARBORETUM CIBUBUR JAKARTA TIMUR - Hasni Ruslan; Christian Flo Ryan Pratama; Imran SL Tobing (LPPM Universitas Negeri Jakarta, 2023)
Urban forest is a special area in anurban planning that plays a role in preserving the environment, as a recreation area and as one of the lungs of the city which helps in maintaining the health of city air. The existence of ants in the urban forest plays a role in maintaining the stability of the urban forest ecosystem which generally has both open and closed habitats. The purpose was to provide information regarding the description of ant species in open and closed habitats in the urban forest of the Cibubur Arboretum, East Jakarta. This research was conducted in the Cibubur Arboretum City Forest, East Jakarta. Sampling was carried out from 5─12 December 2022 using a pitfall trap which was placed in each habitat with a distance between traps of 5 m. As many as 14 ant species are tramp ants which have high adaptability to environmental disturbances. Of the 14 species found, 12 species were not found in closed habitats, namely, Camponotus arrogans and Polycharis becarrii. Pheidole parva was found in open habitats, meanwhile, in closed habitats, Odontoponera denticulata was found in the highest number.